Benefits from the VOIP Use: a case study at GM - Cristofoli, Fulvio; Junior, Antonio Carlos Lago; Feitera, Carlos Henrique (Review of Business Management, 2007)
This article brings a vision about Voip, as well as itself main applications, the factors with that the companies search to decrease costs in telephony, the advantages and disadvantages, aggregation of new technologies as wi-fi to the VOIP and the future of the telephony in Brazil. The differences between Telephony IP and VOIP will be analyzed parallel, and will be showed with as base study case of the General Motors. Our objective for this subject is to show the content that involves this fantastic technology. We can say that will to approach this subject it was influenced not only by being an innovative technology that comes substituting the conventional telephony, reducing the costs of the companies, and changing to services and obsolete equipments for a series of new services offering many resources and benefits, but it also called-us the attention for the fact being a technology whom making a revolution in telecommunications market where the rendering companies of telephony of services consumes a good part of the income of the companies and people, and also for This article brings a vision about VOIP, as well as its main applications, the factors with that the companies search to decrease costs in telephony, the advantages and disadvantages, aggregation of new technologies as wi-fi to the VOIP and the future of the telephony in Brazil. The differences between Telephony IP and VOIP will be analyzed in parallel, and will be showed having as base a case study of the General Motors. Our objective for this subject is to show the content that involves this fantastic technology. We can say that the will to approach this subject was influenced not only by being an innovative technology that comes to substitute the conventional telephony, reducing the costs of the companies, and changing services and obsolete equipment for a series of new services offering many resources and benefits, but it also called us the attention for the fact that this is a technology making a revolution in telecommunications market where the rendering companies of telephone services consumes a good part of the income of the companies and people, and also for demanding in this period of transition a great deal of ability to adequate the necessities of the customer to use of these tools and resources. Key-words: Strategy. VOIP. Information technology (IT). Telephony. Competitiveness.